The Ruling on Removing a Partner from a Company: An Applied Legal and Jurisprudential Study - Al-Khatib, Maryam Ahmed Ghaleb; Tawalbeh, Afnan Yousef Ibrahim; Al-rosan, Nusaiba Dyab Mohammad Al-rosan; Alajlouni, Abdelmahdi Moh’d Said A. (Journal of Posthumanism, 2025)
The objective of this study was to elucidate the legal principles governing the removal of a partner from a company within the context of Islamic jurisprudence and law. The study also elucidated the rationales underlying the removal of a partner from a company, as viewed through the lens of Islamic jurisprudence and subsequent legal implications. The analysis further expounds on pertinent cases in Jordanian courts that address this subject. The study employed a descriptive approach, drawing from both the inductive and analytical approaches. The inductive approach entailed a procedural examination of material in Islamic jurisprudential sources and references, citing the opinions and evidence of Islamic jurists. The analytical approach involved a procedural definition of the partnership and its rulings, an explanation of the forms of removing a partner from a company, and an analysis and discussion of texts and evidence. The study concluded that Islamic jurisprudence does not stipulate the expulsion of a partner from the company in cases of immorality and transgression. Rather, it stipulates the dissolution of the company contract in the event that one of the partners leaves the company for any reason. The researchers attribute this phenomenon to the historical composition of companies, which were typically comprised of two or three entities and did not reach the scale of modern corporations. In the context of dissolution, the possibility of the contracting parties establishing a new company was discussed. Jordanian law explicitly stipulates the permissibility of expelling a partner from a company if evidence indicates justifiable grounds for dismissal, while also considering the interests of both the company and the individual partner. The final decision regarding the expulsion of a partner rests with the court, which must determine whether the evidence substantiates the expulsion. The court may rule to dissolve the contract if the company is unable to continue operating, as each case is adjudicated on its own merits.